Pengembangan Aplikasi “Change-Lab” dalam Meningkatkan Kemampuan Kognitif Siswa Kelas IV pada Materi Perubahan Benda dan Sifatnya - Hani Farihan Apriliani; Regina Lichteria Panjaitan; Aah Ahmad Syahid (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Students' cognitive understanding of Science and Social Studies (IPAS), particularly on the topic of changes in matter and its properties, remains relatively low, while the availability of learning media in elementary schools is still limited. This study aimed to develop an interactive learning medium in the form of an application to improve the cognitive understanding of fourth-grade elementary school students. The study employed the Research and Development (R&D) method using the 4D model, which consists of the define, design, develop, and disseminate stages. Data were collected through interviews, validation questionnaires, student response questionnaires, and learning achievement tests. The results showed that the Change-Lab application obtained a material expert validation score of 95.89% and a media expert validation score of 94.35%, both categorized as highly valid. The study involved 33 students at SDN Nagreg 02. Student responses to the Change-Lab application reached 93.2%, indicating a very positive category, while the N-Gain score of 77.46% demonstrated a significant improvement in students' cognitive understanding. Therefore, the Change-Lab application is effective in improving students' cognitive understanding and is highly suitable for use in fourth-grade IPAS learning.